PENILAIAN RISIKO KERJA MENGGUNAKAN METODE HIRARC DI PT. SINAR LAUT INDAH NATAR LAMPUNG SELATAN - Desianna, Dwi; Yushananta, Prayudhy (Poltekkes Kemenkes Tanjung Karang, 2020)
PT Sinar Laut Indah is a concrete manufacturing plant that has a risk of occupational accidents and occupational diseases due to exposure to particulates, use of work tools, and work methods. The purpose of this research is to find out what are the dangers in a factory, to assess the risk (risk assessment) and risk control (risk control) at each work stage using the HIRARC method.The work risk assessment uses the HIRARC method, which consists of three stages of assessment, namely hazard identification, risk assessment and risk control. The research subjects were all activities in the paving block production section including tools, materials and work processes. Data collection was carried out by observing and measuring exposure, which was then standardized using two risk assessment parameters, namely probability/likelihood of hazard and severity of the hazard. Risk control is the final stage formulated based on the results of the risk assessment from the previous stage.The results of the study found 4 activities in the high category, mixing and stirring of materials, checking rolling boxes, paving blocks presseing, and cleaning the remaining material. The highest risk of occupational diseases is respiratory problems and skin or eye irritation during the mixing and stirring activities of the ingredients, as well as cleaning the remaining materials. Meanwhile, the highest risk of work-related accidents is in rolling box-checking activities.The use of the HIRARC method and the application of probability/likelihood of hazard and severity of hazard are good enough to assess the risk of occupational accidents and occupational diseases. Carrying out repair and maintenance of machines, determining danger zones, using personal protective equipment, and administrative controls are efforts that must be made to avoid risks due to work